The Expressions of the Immunity- and Muscle Development-Related Genes of 40-Day-Old Broilers Are Promoted in Response to the In Ovo and Dietary Supplemental Administration of Calcidiol in Conjunction with the In Ovo Administration of Marek’s Disease Vaccine - Seyed Abolghasem Fatemi; April Waguespack Levy; Edgar David Peebles (Animals)
Effects of in ovo and dietary sources of calcidiol (25(OH)D3), combined with Marek’s disease vaccine (MDV), on the expression of genes involved with the antioxidant activity, muscle deposition, and immunity in the pectoralis major (P. major) muscle and spleen of 40 d of age (doa) broilers were investigated. The in ovo treatments were as follows: (1) non-injected; (2) the injection of 50 μL of commercial MDV, (3) MDV + 1.2, or (4) 2.4 μg of 25(OH)D3. All birds received either a commercial diet containing no supplemental 25(OH)D3 (control) or the same diet supplemented with an additional 69 µg of 25(OH)D3 per kg of feed (Hy-D diet). At 40 doa, the pectoralis major (P. major) muscle and spleen of 48 birds (six replicates per diet x in ovo treatment combination) were collected. When compared to un-supplemented commercial diet-fed birds, in birds that were fed the Hy-D diet, the expression of the TGF-β4 gene in the spleen and P. major muscle, and the GSH-P1, GSH-P7, SOD2, MyoG, MyoD1, and Pax3 genes in the P. major muscle were up-regulated, whereas the expression of the IL-1β, IL-8, and CYP24A1 genes in the spleen and P. major muscle were down-regulated. Nevertheless, birds that received any of the in ovo injection doses of 25(OH)D3 exhibited a higher expression of the IL-10, TGF-β4, and CYP27B1 genes in the spleen and P. major muscle. Furthermore, in comparison to the MDV-injected control group, the CAT, MyoD1, and Pax3 genes in the P. major muscle were up-regulated, and the expression of the INF-γ, IL-1β and CYP24A1 genes in the spleen and the IL-8, and IL-1β genes in the P. major muscle were down-regulated. In conclusion, a significant improvement in the expression of genes responsible for enzymatic antioxidant activity, protein synthesis, and inflammatory reactions in 40-day-old broilers occurred in response to in ovo and dietary supplemental 25(OH)D3, and supplemental 25OHD3 provided via either route was used to enhance the expression of genes linked to vitamin D activity (CYP27B1, CYP24A1).